2016
DOI: 10.3109/13880209.2015.1103755
|View full text |Cite
|
Sign up to set email alerts
|

C-Geranylated flavonoids fromPaulownia tomentosafruits with antimicrobial potential and synergistic activity with antibiotics

Abstract: Context C-6-Geranylated flavonoids possess promising biological activities. These substances could be a source of lead compounds for the development of therapeutics. Objective The study was designed to evaluate their antibacterial and antileishmanial activity. Materials and methods C-6-Geranylated flavanones were tested in micromolar concentrations against promastigote forms of Leishmania brazilensis, L. donovani, L. infantum, and L. panamensis against methicillin-resistant Staphylococcus aureus (MRSA); and sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…aureus . Out of them, mimulone ( 81 ), (geranylated flavonoids) was more effective than the oxacillin (antibiotic standard) with MIC values of 2/4.9 μg/ml (Navrátilová et al, ). The relationship between lipophilicity and the structure of flavonoid analogues in growth inhibition of Gram‐positive and Gram‐negative bacteria were evaluated by flavones from Heliotropium filifolium .…”
Section: Antibacterial Activity Of Flavonoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…aureus . Out of them, mimulone ( 81 ), (geranylated flavonoids) was more effective than the oxacillin (antibiotic standard) with MIC values of 2/4.9 μg/ml (Navrátilová et al, ). The relationship between lipophilicity and the structure of flavonoid analogues in growth inhibition of Gram‐positive and Gram‐negative bacteria were evaluated by flavones from Heliotropium filifolium .…”
Section: Antibacterial Activity Of Flavonoidsmentioning
confidence: 99%
“…aureus with FIC: 0.3–0.5. Navrátilová et al () evaluated the antibacterial activity of 3′‐O‐methyldiplacol ( 100 ) alone and in combination with oxacillin against MRSA strain. Based on MIC/Minimum Bactericidal Concentration (MBC) result (4/4 and 2/4 μg/ml, alone, and combined, respectively), this combination had a synergistic effect against MRSA and this compound was more potent than the standard drug.…”
Section: Antibacterial Activity Of Flavonoidsmentioning
confidence: 99%
“…The antiparasitic activities of Paulownia C-geranylated flavonoids mainly involved the effects of seven unmodified C-geranylflavanones on Leishmania species, including mimulone (1), diplacone (2), 3′-Omethyldiplacone (4), 3′-O-methyl-5′-hydroxydiplacone (5), 3′-O-methyl-5′-O-methyldiplacone (6), 4′-O-methyldiplacone (7), and 3′-O-methyldiplacol (15). Compounds 4 and 6 achieved significant antileishmanial activity with IC 50 values of 10.4 and 12.7 μM against L. donovani, and 11.3 and 8.0 μM against L. braziliensis, respectively, compared with 9.5 and 6.7 μM of miltefosine as the positive control (Navrátilová et al 2016). Furthermore, diplacone (2) was also active (IC 50 1.4 µg mL −1 ) against the related kinetoplastid parasite Trypanosoma brucei brucei (Salem et al 2011).…”
Section: Antiparasitic Activitiesmentioning
confidence: 99%
“…Epidemiological studies revealed that an increased daily intake of phenolic compounds in dietary supplements act as anti-oxidant and anti-inflammatory agents to increase thermogenesis and energy expenditure while decreasing inflammation and oxidative stress, further supporting progress towards decreased metabolic disorders [ 1 , 5 ]. Previous studies confirmed that the species of the genus Paulownia (belonging to the family scrophulariaceae) exhibited a broad spectrum of biological effects, including antioxidant, anticarcinogenic [ 6 , 7 ], antiphlogistic [ 8 ], antiviral [ 9 ], antimicrobial [ 10 ] and anti-cholinesterase activities [ 11 ]. Paulownia fortunei (Seem.)…”
Section: Introductionmentioning
confidence: 99%
“…Hemsl. is a fast growing ornamental tree, native to Mainland China and distributed almost all over the world [ 10 ]. This species is renowned as a polyphenol rich plant, which has been used in traditional Chinese medicine for the treatment of hypertension, enteritis, tonsillitis, bronchitis and dysentery [ 7 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%